Epidemiology of maxillofacial injuries at a regional hospital in Goiania, Brazil, between 2008 and 2010 - Cláudio Maranhão Pereira; Mauro Silva Filho; Danilo Santos Carneiro; Renan Correia Arcanjo; Leonardo Araújo de Andrade; Michelle Gomes Benício de Araújo (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: Facial lesions assume an outstanding role in the attendance of polytraumatized patients in hospital emergency services. The aim of this study was to conduct and epidemiologic study of patients attended at the Buccomaxillofacial Surgery and Traumatology Service of a regional hospital in Goiania/GO, Brazil, between 2008 and 2010. Material and methods: 521 files of patients, who had suffered maxillofacial traumatisms that resulted in a total of 615 fractures, were evaluated. The files were used to analyze gender, age, etiologic agents and distribution of fractured bones. Results: About 80% of patients were male, whereas 20% of the affected individuals were women. The most frequently etiologic factor found in the two groups was automobile accidents, followed by physical aggressions and falls. Concerning to fractured bones, the zygomatic complex, followed by fractures of the mandible, the nasal bones themselves, condyle and Le Fort type fractures were the most prevalent ones, in both groups. Conclusion: Knowledge of the incidence and etiology of maxillofacial fractures is of great importance to the professionals involved in the treatment of these patients. Within this context, Buccomaxillofacial Surgery and Traumatology is increasingly being affirmed as one of the most important specialties at the emergency centers of regional hospitals concerning to the treatment of patients who are victims of traumatisms.